2010
DOI: 10.1097/aco.0b013e32833853e8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of chronic pain after labor and delivery

Abstract: Treatment of acute pain during labor and delivery is necessary to prevent chronic pain. Future studies should focus on the long-term effects of different analgesic regimens on the development of chronic pain after labor and delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 23 publications
0
47
0
1
Order By: Relevance
“…Conversely, higher postdelivery pain following casesarean section was indeed found to be a predictor of chronic pain [76]. Some investigators believe that surgery, by cutting nerves or initiating prolonged inflammatory reactions, is the major determinant of CPSP [77]. Although no large prospective trial has confirmed that any specific anaesthetic intervention reduces the risk of CPSP, there is some evidence in smaller trials.…”
Section: Perioperative Pain Management and The Development Of Chronicmentioning
confidence: 99%
“…Conversely, higher postdelivery pain following casesarean section was indeed found to be a predictor of chronic pain [76]. Some investigators believe that surgery, by cutting nerves or initiating prolonged inflammatory reactions, is the major determinant of CPSP [77]. Although no large prospective trial has confirmed that any specific anaesthetic intervention reduces the risk of CPSP, there is some evidence in smaller trials.…”
Section: Perioperative Pain Management and The Development Of Chronicmentioning
confidence: 99%
“…Chronic pain (persistent incisional pain > 3 months after surgery) is reported to occur in approximately 10% of patients undergoing surgery [8,9]. A consistent finding in postoperative pain studies is an association between severe, acute, postoperative pain and the likelihood of ongoing persistent incisional pain [9,10]. "Dynamic" experimental pain tests attempt to show the strength of an individual's endogenous inhibitory nociceptive pathways (diffuse noxious inhibitory controls), and the propensity for nociceptive excitation or sensitization (temporal summation) [5,11].…”
Section: Experimental Pain Testsmentioning
confidence: 95%
“…It may be in part a failure of the nervous system to return to its initial settings before the injury [10]. Even in a single case of surgery different mechanism might be involved [11]. Usually chronic pain has their origins in an episode of acute pain which is particularly true of chronic pain after surgery.…”
Section: Mechanism Of Cpopmentioning
confidence: 99%